Aplikasi Model Pembelajaran Explicit Instruction dalam Pengembangan Modul Menulis Cerpen - Putra, Hermansah; Fitriani, Yessi; Utami, Puspa Indah (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Grade 5 students of SD Negeri 88 Ogan Komering Ulu do not yet have a short story writing module. For this reason, the purpose of this study was to describe the results of the development of the short story writing module by applying the explicit instruction learning model. This research was conducted at SD Negeri 88 Ogan Komering Ulu. The type of research conducted is Research and Development (R&D). The steps taken in this research include research and information gathering, product development, validation testing, product revision, and product testing. The subjects of this research are students, Indonesian language teachers, and lecturers as experts. The tools used are textbook reviews, interviews, questionnaires, and validation forms. Data analysis was carried out by analyzing textbooks, analyzing teacher interviews, analyzing product validation from expert instructors, teachers, and students. The results of this study indicate that: 1) only Indonesian text books are used by teachers in teaching while the short story writing module does not yet exist, 2) the explicit instruction learning model in the development of the short story writing module is feasible from the aspects of material, presentation, language, and graphics, and 3) the module entitled Writing Short Stories Based on the Explicit Instruction Learning Model for Elementary School Students in Grade 5 is declared to be able to be used.